2011
DOI: 10.4321/s1130-01082011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Safety of continuous propofol sedation for endoscopic procedures in elderly patients

Abstract: Objective: to evaluate safety of continuous propofol sedation in elderly patients who undergo endoscopic procedures and investigate risk factors to develop complications in the geriatric population.Material and methods: patients who received endoscopistdirected propofol sedation were classified into two groups according to age. Group I: > 80 years; Group II: < 80 years. Propofol was administered by continuous intravenous infusion to achieve deep sedation. Arterial oxygen saturation, heart rate, blood pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
0
28
0
5
Order By: Relevance
“…An initial bolus of propofol (dose adapted to patient weight, age or comorbidity) is administered intravenously, followed by repeated boli according to desired sedation depth and the patient condition. Scarce scientific evidence is available on NAAP using continuous infusion systems for colonoscopy so far now (6)(7)(8). According to our hypothesis, continuous infusion of propofol might exert a more sustained sedative effect by maintaining a preset concentration of propofol in the blood or brain, providing a higher patient satisfaction with the procedural sedation.…”
Section: Introductionmentioning
confidence: 99%
“…An initial bolus of propofol (dose adapted to patient weight, age or comorbidity) is administered intravenously, followed by repeated boli according to desired sedation depth and the patient condition. Scarce scientific evidence is available on NAAP using continuous infusion systems for colonoscopy so far now (6)(7)(8). According to our hypothesis, continuous infusion of propofol might exert a more sustained sedative effect by maintaining a preset concentration of propofol in the blood or brain, providing a higher patient satisfaction with the procedural sedation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when taken in context, the complication rate is still quite low even for patients over 85 years of age, and in most cases colonoscopy can be done safely with appropriate monitoring and precautions [20] . Furthermore, several studies have shown that propofol sedation, despite its propensity to lower blood pressure, can be used safely in elderly patients [21][22][23] . The overall major Lin OS.…”
Section: Eventsmentioning
confidence: 99%
“…Furthermore, Correia et al [21] reported results in concordance with results of the present work. Moreover, Martinez et al [22] reported that, continuous propofol sedation in geriatrics [patients >80 years] is generally as safe as in younger populations, although, geriatrics are more prone to complications. Singh et al [23] conducted a metaanalysis of 20 studies for sedation in cirrhotic patients and showed that, recovery time was shorter with propofol use than midazolam.…”
Section: Methodsmentioning
confidence: 99%